2009
DOI: 10.2174/1876397900901010093
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Concnetrations in Sediment and Periwinkle -Tympanotonus fuscastus in the Different Ecological Zones of Bonny River System, Niger Delta, Nigeria

Abstract: Studies of total hydrocarbon concentrations (THC) and heavy metals was conducted at the Bonny /New Calabar River in order to determine the level of these contaminants (from municipal and industrial sources) on sediment and important biological organism in the environment in September 2000 for wet and January 2001 for dry seasons. The study area is within the eastern arm of the Niger Delta located between longitude 40 25" to 40 40" N and latitude 70 25" to 70 15" E. In the 3 ecological areas studied, the distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…This assessment revealed that the concentration of Ni is below those in New Calabar River, Rivers State of Nigeria, where its value is 4.537±0.427mg/Kg but above those of Bodo Creek [50,51]. However, Maa-Dee-River shows no significant difference with other rivers within Niger Delta [55,56]. It is lower than the permissive limit for Ni set by DPR.…”
Section: Distribution Of Heavy Metals In Riverine Sediments Of the Sa...mentioning
confidence: 81%
“…This assessment revealed that the concentration of Ni is below those in New Calabar River, Rivers State of Nigeria, where its value is 4.537±0.427mg/Kg but above those of Bodo Creek [50,51]. However, Maa-Dee-River shows no significant difference with other rivers within Niger Delta [55,56]. It is lower than the permissive limit for Ni set by DPR.…”
Section: Distribution Of Heavy Metals In Riverine Sediments Of the Sa...mentioning
confidence: 81%
“… [80] Chindah2009 Bonny and New Calabar River /Rivers State ICP-AES - Cr (0.002–0.130), Cd (0.0005–0.014), Pb ( 0.009–0.075), Zn (0.294 – 3), Cu (0.63–8.78) mg/kg wet wt. [81] Adebayo-Tayo2010 Itu and Oron Creeks (Oron, Itu LGA) /Akwa Ibom State AAS 120 Fe (17.2 – 22.7), Zn (24.4 – 94.2), Pb (0.28 – 0.84), Cd (0.02 – 0.15), Mn (24.2 – 88.6), Cu (3.4 – 7.4) mg/kg wet wt. [82] Woke2016 Andoni River (Khana LGA) /Rivers State AAS 30 Cd (0.01–0.04), Cu (25 – 30), Pb (0.2–0.55), Zn (22 – 42) mg/kg dry wt.…”
Section: Resultsmentioning
confidence: 99%
“…Geen statisties betekensivolle verskille (p > 0.05) het voorgekom tussen die gemiddelde konsentrasies in die seesterre vanaf die verskillende lokaliteite nie. Die massa-op-massa-BAF vir Cd was 3256 wat daarop dui dat akkumulering sterk in die seesterre plaasgevind het indien dit byvoorbeeld met die waardes vergelyk word watChindah et al (2009) vir Gastropoda in die Niger Delta bepaal het. Die seisoenale gemiddelde konsentrasies vir die baai self het gewissel van 0.12 µg/L in die winter van 2000 tot 1.48 µg/L in die daaropvolgende herfs van 2001.…”
unclassified